(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Phraseological competence, as a crucial component of language proficiency, plays a fundamental role in mastering a foreign language. It encompasses the ability to understand, interpret, and appropriately use idiomatic expressions, collocations, and fixed phrases, which are deeply embedded in the cultural and cognitive framework of native speakers.